2020
DOI: 10.1016/j.isci.2020.101622
|View full text |Cite
|
Sign up to set email alerts
|

Phage-DMS: A Comprehensive Method for Fine Mapping of Antibody Epitopes

Abstract: Summary Understanding the antibody response is critical to developing vaccine and antibody-based therapies and has inspired the recent development of new methods to isolate antibodies. Methods to define the antibody-antigen interactions that determine specificity or allow escape have not kept pace. We developed Phage-DMS, a method that combines two powerful approaches—immunoprecipitation of phage peptide libraries and deep mutational scanning (DMS)—to enable high-throughput fine mapping of antibody … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 39 publications
(61 reference statements)
0
42
0
Order By: Relevance
“…Lineage 105 targets the V3 loop and there were changes in this region among the QA255 Env sequences, although it was unknown if the sequence changes would impact binding of 105 to its epitope. To address this, we finely mapped the epitope and sites of escape for both the mature and naive mAbs using a phage-display deep mutational scanning (Phage-DMS) approach ( Garrett et al, 2020 ). The mAbs were screened using a library displaying gp41 and V3 peptides from HIV strains BG505.W6M.C2 (clade A), BF520.W14M.C2 (clade A), and C.ZA.1197MB (clade C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lineage 105 targets the V3 loop and there were changes in this region among the QA255 Env sequences, although it was unknown if the sequence changes would impact binding of 105 to its epitope. To address this, we finely mapped the epitope and sites of escape for both the mature and naive mAbs using a phage-display deep mutational scanning (Phage-DMS) approach ( Garrett et al, 2020 ). The mAbs were screened using a library displaying gp41 and V3 peptides from HIV strains BG505.W6M.C2 (clade A), BF520.W14M.C2 (clade A), and C.ZA.1197MB (clade C).…”
Section: Resultsmentioning
confidence: 99%
“…Profiling of escape mutations was done as previously described ( Garrett et al, 2020 ). We utilized a deep mutational scanning (DMS) phage display library containing wildtype and mutant peptides that tile across the gp41 and V3 portions of three Envelope strains (BG505.W6M.C2, BF520.W14M.C2, and C.ZA.1197MB).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,820 unique peptides were designed in total; the peptide library included wildtype peptides that could be used to define the antibody epitope and peptides with all possible mutations to determine those within the defined epitope that disrupt or enhance antibody binding. Two biological replicate libraries of these peptide sequences were cloned as we have done previously (Garrett et al, 2020). Deep sequencing of the final duplicate libraries (Library 1 and Library 2) indicated that each contained a high percentage of all unique sequences (96.0% and 95.9%, respectively) (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Complexes of antibodies that bind the phage library are immunoprecipitated and sequenced to determine the antibody binding region(s) and the mutations within that epitope region that disrupt binding. Phage-DMS has several advantages: it is high-throughput, allowing comparison amongst a large number of samples in parallel, it can determine pathways of escape for both neutralizing and non-neutralizing antibodies that bind to linear epitopes, and results using this method also correlate well with mutational effects measured in other assays (Garrett et al, 2020). Here, we used Phage-DMS to understand the spectrum of single mutations on the S protein that could reduce antibody binding and thus mediate escape from plasma antibodies found in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%